The Status of Education for Sustainability in Initial Teacher Education Programs: A Canadian Case Study. Issue 4 (19th August 2014) - Falkenberg, Thomas; Babiuk, Gary; Leal Filho, Walter; Sima, Mihaela
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The purpose of this paper is to establish the status of education for sustainability in the teacher education programs in the province of Manitoba in Canada and to identify challenges and obstacles for mainstreaming education for sustainability in those programs. Design/methodology/approach Using a multi-unit case study design, on-line program information and data from interviews with faculty administrators and a convenience sample of faculty members from all five faculties of education in Manitoba were collected and analysed. Findings There is no systematic and focused preparation of teachers for education for sustainability in any of the Manitoba teacher education programs. Three challenges for mainstreaming of education for sustainability are identified: lack of leadership, an unfavourable view of the role of education for sustainability, and the silo-ing within faculties of education. Research limitations/implications The research is limited by its focus on the program-based implementation of education for sustainability in faculties of education, which did not include any course-based implementation by individual instructors. Practical implications To address the challenges and obstacles for mainstreaming, the authors argue for joint leadership across the relevant institutional levels (government, university, and faculty), and for establishing education for sustainability as a framework for responding to the purpose question of school education. Originality/value The study provides empirical evidence for some of the major challenges for mainstreaming education for sustainability in faculties in education and, by generalization, all university faculties.